Antimicrobial activity of glycosidase inhibitory protein isolated from Cyphomandra betacea Sendt. fruit - Ordóñez, Roxana Mabel (2006)
Broad-spectrum antimicrobial activity of an invertase inhibitory protein (IIP) isolated from Cyphomandra betacea ripe fruits is documented. Minimal inhibitory concentration (MIC) values were determined by agar macrodilution and broth microdilution assays. This IIP inhibited the growth of xylophagous and phytopatogenic fungi (Ganoderma applanatum, Schizophyllum commune, Lenzites elegans, Pycnoporus sanguineous, Penicillium notatum, Aspergillus niger, Phomopsis sojae and Fusarium mango) and phytopathogenic bacteria (Xanthomonas campestris pvar vesicatoria CECT 792, Pseudomonas solanacearum CECT 125, Pseudomonas corrugata CECT 124, Pseudomonas syringae pv. syringae and Erwinia carotovora var carotovora). The IIP concentration required to completely inhibit the growth of all studied fungi ranged from 7.8 to 62.5 μg/ml. Phytopatogenic bacteria were the most sensitive, with MIC values between 7.8 and 31.25 μg/ml. Antifungal and antibacterial activities can be associated with their ability to inhibit hydrolytic enzymes. Our results indicate the possible participation of IIP in the plant defense mechanism and its potential application as a biocontrol agent against phytopathogenic fungi and bacteria. © 2005 Elsevier Inc. All rights reserved.